HUBUNGAN FAKTOR PENERIMAAN APLIKASI UJIAN SEKOLAH BERBASIS KOMPUTER MENGGUNAKAN MODEL UTAUT - Aris Puji Widodo; Rahmat Gernowo (Universitas Muhammadiyah Semarang, 2017)
Information Technology (IT) implementation has been applied in various areas of life, including education. The field of education of any IT application is toorganize a computer-based school exam model. Computer-based school examsprincipally refer to all paper-based test processes, such as questioning, testexecution, and promising results. This paper discusses the relationship offactors that affect the acceptance of the use of computer-based school examapplications using Unified Theory of Acceptance and Use of Technology(UTAUT). Data analysis techniques using Structural Equation Model (SEM,) todetermine the relationship of UTAUT factors that affect the acceptance ofcomputer-based school exam applications.The number of respondents used asmuch as 132 taken from users of computer-based school exam applications. Theresult of descriptive analysis shows that Performance Expectancy (PE), SocialInfluence (SI) and Facilitating Condition (FC) have significant influence onBehavioral Intention variable, while Effort Expectancy (EE) variable hasinsignificant influence. Keywords: UTAUT, SEM, Acceptance, Exam, and School,